Training Psychologists for Rural Practice: Exploring Opportunities and Constraints. Issue 1 (17th April 2018) - Domino, Marisa Elena; Lin, Ching‐Ching Claire; Morrissey, Joseph P.; Ellis, Alan R.; Fraher, Erin; Richman, Erica L.; Thomas, Kathleen C.; Prinstein, Mitchell J.
Abstract: Purpose: To examine trends in the psychologist workforce and training opportunities, including factors that may influence the decision of clinical psychologists to practice in rural settings. Methods: We use a mixed‐methods approach to examine the psychologist workforce nationally and in North Carolina (NC), including (1) an analysis of the location of programs awarding doctoral degrees; (2) an analysis of the practice, demographic, and educational characteristics of the psychologist workforce; and (3) interviews with directors of doctoral programs in clinical psychology to understand where current graduates are getting jobs and why they may or may not be choosing to practice in rural communities. Findings: Fewer than 1% of programs and institutions awarding doctoral degrees in psychology in the United States are located in rural areas. In NC, approximately 80% of practicing psychologists have out‐of‐state degrees and about 80% of recent NC graduates are not currently licensed in the state. This juxtaposition undermines the utility of adding more in‐state degree programs. While expansion of training programs within rural areas could help alleviate the shortages of mental health providers, adding new degree‐granting programs alone will not necessarily increase supply. We discuss complementary recruitment and retention strategies, including greater incentives for rural training and practice as well as training in emerging technologies that don't require providers to be physically located in underserved areas, such as telemedicine. Conclusions: Increasing the supply of psychologists practicing in rural areas will require a thoughtful, multipronged approach to training this critical part of the behavioral health workforce.